Prevalence and associated factors of medication adherence among infertile women undergoing frozen-thawed embryo transfer cycle: A cross-sectional study - Ni, Ying; Tong, Chenye; Xu, Lianying; Qian, Wen; Huang, Limin; Zhang, Aijun; Fang, Qiong (Frontiers in Pharmacology, 2023)
Objective: This study aimed to explore the prevalence and associated factors of medication adherence among infertile women undergoing frozen-thawed embryo transfer (FET) cycle. Methods: A cross-sectional study was conducted with 556 infertile women undergoing FET cycle in total. The Self-efficacy for Appropriate Medication Use Scale (SEAMS), Herth Hope Index (HHI) scale, and Social Support Rating Scale (SSRS) were used to evaluate the patients. Data were described by univariate and multivariate analyses. Logistic regression method was performed to analyse the factors potentially associated with medication adherence. Results: The average score of Self-efficacy for Appropriate Medication Use Scale (SEAMS) was 30.38 ± 6.65, and 65.3% of participants showed non-adherence. Multiple regression analysis indicated that first-time FET cycle, treatment stage, methods of daily medication, social support and hope level were the main associated factors of the medication adherence among infertile women undergoing FET cycle (P < 0.001). Conclusions: This study revealed the medication adherence is at medium level among infertile women undergoing FET cycle, especially in patients with repeated FET cycles. The study also suggested that improving the hope level and social support of infertile women undergoing FET cycle may increase medication adherence.